1992
DOI: 10.1093/oxfordjournals.annonc.a058233
|View full text |Cite
|
Sign up to set email alerts
|

Cancer diagnosis disclosure in a Spanish hospital

Abstract: At the Clinic Hospital in Barcelona, Spain, 167 cancer patients and 380 hospital health care workers were interviewed about cancer diagnosis disclosure. Only 25 patients (15%) were correctly informed of their diagnoses. Breast cancer patients were significantly more often informed than patients with other malignancies (p less than 0.05). Two hundred seventy-two of 380 hospital health workers interviewed (71%, p = 0.00) would want to know their own diagnoses should they suffer from cancer in the future, but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…This is in agreement with the findings from Northern Europe and Anglo-Saxon countries where they usually reveal the truth to both patients and their spouse [1,79]. In contrast, it has been found that physicians from Southern and Eastern Europe [11,13,18,20,36,66,69], Africa, France, Iran, Panama, Japan, Singapore and Saudi Arabia [9,52] agree upon the concealment of the truth [30,32,35,41,51,79,85]. However, there is an obvious shift towards disclosure observed in these nations following trends set in the US and the UK.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the findings from Northern Europe and Anglo-Saxon countries where they usually reveal the truth to both patients and their spouse [1,79]. In contrast, it has been found that physicians from Southern and Eastern Europe [11,13,18,20,36,66,69], Africa, France, Iran, Panama, Japan, Singapore and Saudi Arabia [9,52] agree upon the concealment of the truth [30,32,35,41,51,79,85]. However, there is an obvious shift towards disclosure observed in these nations following trends set in the US and the UK.…”
Section: Discussionsupporting
confidence: 91%
“…At the beginning of the 1980s, while most doctors in northern Europe and in other Anglo-Saxon countries were already revealing the diagnosis both to the patient, and (with the patient's permission) the spouse, in Southern and Eastern Europe, doctors maintained an attitude of concealment from the patient [11,13,20,36,66,69]. This attitude was also present in Greece where the majority of doctors (87.5%) concealed the truth from their patients, although 74% believed that the patient had the right to be aware of his/her illness [18,70].…”
Section: Introductionmentioning
confidence: 99%
“…The change was not because of a significant change in patients' wishes, as early surveys showed that most patients wanted to know the truth [33]. At the beginning of the 1980s, although most doctors in Northern Europe and in other Anglo-Saxon countries were ready to reveal diagnoses both to the patient and relatives, practice in Southern and Eastern Europe were less consistent [26,34]. For example, a report from Greece published in 1986 found that the majority of doctors (87.5%) concealed the truth from their patients, although only 74% believed that the patient had the right to be aware of his/her illness [35].…”
Section: What Do Clinicians Want To Reveal or Actually Reveal?mentioning
confidence: 99%
“…In Northern and Western European countries, information about medical diagnoses and prognoses are revealed straightforward, whereas in the Southern and Southeastern European countries, doctors rather prefer to leave patients uninformed [15,23,35,39]. Especially in non-Western European countries, disclosure rates of less than 50 % had been reported [32,37].…”
Section: Introductionmentioning
confidence: 99%